COVID-19 vaccination hesitancy and willingness among pregnant women in Italy - Miraglia del Giudice, Grazia; Folcarelli, Lucio; Napoli, Annalisa; Corea, Francesco; Angelillo, Italo Francesco, The Collaborative Working Group; Agangi, Annalisa; Sciambra, Antonio; Scognamiglio, Glenda; Longanella, Walter (Frontiers in Public Health, 2022)
Background: Pregnant women, especially those with comorbidities, compared to those non-pregnant, have higher risk of developing a severe form of COVID-19. However, COVID-19 vaccine uptake is very low among them. Methods: An anonymous questionnaire was administered to randomly selected women 18 years of age that were currently pregnant or had just given birth between September 2021 and May 2022 in the geographic area of Naples. Vaccine hesitancy was assessed using the vaccine hesitancy scale (VHS). Results:A total of 385 women participated to the study. Women who did not have contracted SARS-CoV-2 and who need information about vaccination against COVID-19 had a higher perceived risk of being infected with SARS-CoV-2. More than half (54.3%) of the women were very afraid of the potential side effects of the vaccination against COVID-19 on the fetus. Higher concern of the side effects of the vaccine on the fetus was among those who did not get a graduate degree, in pregnant at risk, in those who had not contracted SARS-CoV-2, in those who were more concerned that they couldbe infected by SARS-CoV-2, in those who did not know that this vaccination was recommended for them, and in those trusting mass media/internet/social for information. Only 21.3% were vaccinated when pregnant, particularly women with a university degree, who have contracted SARS-CoV-2 before pregnancy, who did not need information, and who have acquired information about vaccination from gynecologists. Almost three-quarters (71.9%) were willing to receive the vaccination and were more likely those with a university degree, who knew someone who had contracted SARS-CoV-2, who were more concerned that they could be infected by SARS-CoV-2, and who were not extremely concerned of the side effects of the vaccine on the fetus. A total of 86.4% were high-hesitant. Respondents who did not get a graduate degree, those less concerned that they could be infected by SARS-CoV-2, and those trusting mass media/internet/social for their information were high-hesitant. Conclusion: Public health efforts and education campaigns on pregnant women are needed for changing their perception patterns and for supporting gynecologists in promoting the uptake of this vaccination.